Musibah dalam Perspektif Al-Qur’an (Pendekatan Tafsir Maudu’i) - Mustajib Daroini; Tutik Hamidah (Qur'an and Hadith Academic Society, 2021)
This article discusses the theme about calamity because it has many terminologies that indicate the meaning of disaster; such as the words Balā', slander, Ażāb, Ba's, Rijz and Ḍarrā'. The word calamity generally returns to the natural causes that make it possible. The division is divided into two parts, the first what can be considered as sunnatullah Almighty in the universe, the second, second, is what is considered human error. The form of calamity can be classified into two main groups, namely good (positive) and bad (negative) calamities. In general, there are two types of disaster objects, first for world renewal and the second for improving human performance. As for the benefits of this disaster, it is to elevate humanity, eliminate degeneration, and instill sincerity in the hearts of the seasoned people and teach them to be serious in Islamic preaching so that they reach the highest level of heaven, and when the disaster is good (positive) descending humans must show praise and gratitude to Allah SWT, and when the disaster is bad (Negative), humans should know that it is actually a test (relaxation) from Allah SWT and accept it with patience and submission, Allah ‘Azzā Wajallā will honor those who are patient with brilliant glory in love, compassion and Hidayah.